Arthroscopic Repair of Humeral Avulsion of Glenohumeral Ligament Lesions: Outcomes at 2-Year Follow-up. Issue 8 (5th August 2021) - Grundshtein, Alon; Kazum, Efi; Chechik, Ofir; Dolkart, Oleg; Rath, Ehud; Bivas, Assaf; Maman, Eran
Background: Humeral avulsion of the glenohumeral ligament (HAGL) is an uncommon condition but a major contributor to shoulder instability and functional decline. Purpose: To describe the pre- and postoperative HAGL lesion presentations of instability, pain, and functionality and the return-to-sports activities in patients managed arthroscopically for anterior and posterior HAGL lesions. Study Design: Case series; Level of evidence, 4. Methods: Data on patients with HAGL lesions treated with arthroscopic repair between 2009 and 2018 were retrospectively retrieved from medical charts, and the patients were interviewed to assess their level of postoperative functionality. The Rowe; Constant; University of California, Los Angeles; Oxford; and pain visual analog scale (VAS) scores were obtained for both pre- and postoperative status. Return-to-sports activities and level of activities after surgery were compared with the preinjury state, and complications, reoperations, and recurrent instability were recorded and evaluated. Results: There were 23 study patients (12 females and 11 males; mean age, 24 years). The mean follow-up duration was 24.4 months (range, 7-99 months; median, 17 months). In 7 (30.4%) of the patients, HAGL lesions were diagnosed only intraoperatively. A significant improvement was seen in all examined postoperative functional scores and VAS. At the last follow-up visit, 2 patients (8.7%) reported residual instability with no improvement in pain levels and declined any further treatment, and 3 others (13.0%) required revision surgeries for additional shoulder pathologies (reoperations were performed 18-36 months after the index procedure). The remaining 18 patients (78.3%) were free of pain and symptoms. There was a mean of 0.65 coexisting pathologies per patient, mostly superior labral anterior-posterior, Bankart, and rotator cuff lesions. Conclusion: HAGL lesions are often missed during routine workup in patients with symptoms of instability, and a high level of suspicion is essential during history acquisition, clinical examination, magnetic resonance imaging arthrogram interpretation, and arthroscopic evaluation. Arthroscopic repair yields good pain and stability results; however, some high-level athletes may not return to their preinjury level of activity.